Effect of voltage on the consolidation of TiC particulates on steel substrate fused by TIG welding arc - Mridha, Shahjahan; Idriss, A.N.M.; Maleque, Md. Abdul; -, Suryanto; A. Mohamad Al-Batt’hi, Souad (Universiti Malaya, 2012)
Surface alloying with ceramic powder uses a high energy input to create composite coating that provides protection against wear and corrosion. In this work TiC incorporated composite coating was created by melting single tracks in 1.0 mg/mm2 TiC powder preplaced on alloy steel surfaces using a conventional TIG welding torch produced at 80 ampere current with a voltage between 30 to 55 V and a constant traversing speed of 1.0 mm/s. The effect of voltage, used to generate TIG torch for melting, was investigated in terms of geometry, microstructure and hardness of the processed track. The TIG torch produced with different voltages created melt pool of hemispherical shape with varying track dimensions. The melt dimensions increased with increasing the voltage. Glazing with 30 V created a melt pool of 3.10 mm wide and 0.80 mm deep; the maximum width of 3.96 mm and depth of 0.97 mm was produced at 55 V and 45 V, respectively. Tracks produced under different conditions were free from cracks but pores were seen in places. The melt microstructures consisted of partially dissolved and unmelted TiC particulates along with dendrites of a variety of TiC precipitates. Agglomeration of TiC was apparent at the edges. The population of TiC precipitates and partially dissolved TiC particulates increased when glazed at a high voltage torch. Hardness development was lowest when glazed at 30 V and it increased by glazing at 35 and 45 V. The population of TiC particulates and their sizes were seen to influence the hardness and this phenomenon is also similar